A influência da temperatura na secagem forçada da matéria-prima cerâmica da Formação Corumbataí na região do Polo de Santa Gertrudes (SP) - Azzi, Andrezza de Almeida [UNESP] (2014)
The ceramic tiles production in Brazil reached almost 1 billion m² in 2013. More than 60% of these tiles were produced in the Ceramic District of Santa Gertrudes (CDSG). The main advantage of ceramic industries from Santa Gertrudes district is an application of the dry grinding process, which is much more profitable than the wet grinding process, used worldwide. The dry grinding process accounted for 73 % of tiles production in the CDSG in 2013. For the dry route of tiles production, only rocks from Corumbataí Fm. in the region are used, which decreases costs for raw material transportation. On the other hand, the booming ceramic industry in the Santa Gertrudes district has caused air pollution and river silting due to large amount of dust generated by drying and transportation the raw material. Ceramic companies need to replace their current beneficiation areas by industrial dryers. However, the batch whose raw materials were drying forced has produced tiles that break or crack during the industrial process. Three types of raw materials, D (slightly weathered), I (weathered) and M (highly weathered) were examined in the present study in order to better understand the behavior of clays during the drying process. Clay minerals characterization were made using qualitative and quantitative XRD, petrographic studies, infrared spectroscopy (FTIR), thermo gravimetric analysis (DTA-TG-DTG), SEM e TEM. Quantitative XRD analysis showed that D, I and M contain 53, 63 and 64 wt.% of clay minerals, respectively. Illite and smectite are the main minerals, probably with a small amount of mixed-layered illite-smectite. Sample M contains also kaolinite that according to XRD analysis may be accompanied with mixed-layered kaolinite-smectite. Thermal experiment was realized in different temperatures (100°C, 200°C and 300°C) for fraction < 2 μm. Air dried XRD pattern indicated smectite collapses over 100°C. After 200°C and 300°C the ethylene glycol...